2022
DOI: 10.1039/d2gc00918h
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Pd–Au/BNNS bimetallic catalysts for direct generation of H2O2 from H2 and O2 under environmentally friendly conditions

Abstract: Hydrogen peroxide (H2O2) as an important biocompatible oxidant has a wide range of industrial applications including medical, textiles, and water treatment. Pd containing catalysts as active components modified by another...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As an environmentally friendly clean oxidant agent, hydrogen peroxide (H 2 O 2 ) has been widely used in several fields, including pulp bleaching, chemical synthesis, as well as wastewater treatment . At present, H 2 O 2 can be produced by traditional anthraquinone and electrochemical methods, but these methods generally have some defects, such as explosion risk, toxic byproducts, and high energy consumption. , Therefore, it has become very necessary to develop the novel manufacturing technology of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As an environmentally friendly clean oxidant agent, hydrogen peroxide (H 2 O 2 ) has been widely used in several fields, including pulp bleaching, chemical synthesis, as well as wastewater treatment . At present, H 2 O 2 can be produced by traditional anthraquinone and electrochemical methods, but these methods generally have some defects, such as explosion risk, toxic byproducts, and high energy consumption. , Therefore, it has become very necessary to develop the novel manufacturing technology of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers improved the DSHP catalytic performance by incorporating a second component and found that the reaction path could be regulated by nely tuning the electronic environment around the Pd species. 13,17,18,[20][21][22][23] For example, Hutchings and co-workers reported a PdSn/TiO 2 catalyst with a layer of tin oxide wrapped around the surface of small Pd-rich particles synthesized via an appropriate heat treatment cycle, which could shut down the successive hydrogenation and decomposition reactions, thus improving the catalytic performance of Pd in the DSHP. 17 Lewis and co-workers reported that the introduction of base metals into a AuPd catalyst improved the catalytic performance towards the DSHP, attributing the improvement to the modication of the electronic environment of Pd.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] However, it is important to note that more than two-thirds of end-use application demand is for low concentration H 2 O 2 (less than 9 wt%). [11][12][13] Under such circumstances, environmental and economic factors have led to a strong interest in low-scale and low-energy processes to synthesize hydrogen peroxide. 14,15 Compared with conventional processes, the direct synthesis of H 2 O 2 (DSHP) is considered to be a green and appealing alternative clean manufacturing route that can potentially produce H 2 O 2 in a ready-to-use, eco-friendly manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation